Bioenergetic Inhibitors: Antibiotic Efficacy and Mechanisms of Action in Mycobacterium tuberculosis - Hasenoehrl, Erik J.; Wiggins, Thomas J.; Berney, Michael (Frontiers in Cellular and Infection Microbiology, 2021)
Development of novel anti-tuberculosis combination regimens that increase efficacy and reduce treatment timelines will improve patient compliance, limit side-effects, reduce costs, and enhance cure rates. Such advancements would significantly improve the global TB burden and reduce drug resistance acquisition. Bioenergetics has received considerable attention in recent years as a fertile area for anti-tuberculosis drug discovery. Targeting the electron transport chain (ETC) and oxidative phosphorylation machinery promises not only to kill growing cells but also metabolically dormant bacilli that are inherently more drug tolerant. Over the last two decades, a broad array of drugs targeting various ETC components have been developed. Here, we provide a focused review of the current state of art of bioenergetic inhibitors of Mtb with an in-depth analysis of the metabolic and bioenergetic disruptions caused by specific target inhibition as well as their synergistic and antagonistic interactions with other drugs. This foundation is then used to explore the reigning theories on the mechanisms of antibiotic-induced cell death and we discuss how bioenergetic inhibitors in particular fail to be adequately described by these models. These discussions lead us to develop a clear roadmap for new lines of investigation to better understand the mechanisms of action of these drugs with complex mechanisms as well as how to leverage that knowledge for the development of novel, rationally-designed combination therapies to cure TB.